'NOW WALKS LIKE OTHERS': A PRELIMINARY ENQUIRY INTO THE NORTHAMPTON CRIPPLED CHILDREN'S FUND. (October 2013) - Williams, A N; Chan, C
Abstract : Over recent years scholarly interest in the history of childhood, child health and disability has developed and intensified. However, there are still considerable areas which have not been subjected to extensive historical enquiry, such as the treatment and management of 'crippled' children in the UK during the late 19th and early 20th centuries. A key opinion in this study is that of Borsay who has stated that the care of poor 'crippled children' and their families in Victorian England were 'subjected to moral condemnation through a surveillance network funded and managed through the voluntary sector' (Borsay, 2002 ). On-going research using a small case series based on material from Northampton Crippled Children's Fund (NCCF, 1893–1928), Annual Reports dated from 1905 to 1925 and ledgers of surgical records, compared with the monthly contemporary Northampton Neuromuscular Clinic, will challenge this view as being insufficiently nuanced.